Epilepsy - Jinwei Zhang (Exploration of Neuroscience)
Epilepsy, a complex and widespread neurological disorder, has evolved in its understanding from ancient misconceptions to modern scientific advancements. This special issue highlights pivotal research and reviews on the mechanisms underlying epilepsy, innovative treatment strategies, and the psychosocial dimensions of living with this condition. Together, these contributions reflect the growing interdisciplinarity and depth in epilepsy research.